Menguatkan Ekonomi Desa Berbasis Kearifan Lokal Melalui BUMDes: Studi Kasus di Desa Grenggeng Kabupaten Kebumen - Nurwanto, Imam (Sahabat Akademia Group, 2025)
This study aims to describe the process of strengthening the village economy based on local wisdom through the Village-Owned Enterprise (BUMDes) in Grenggeng Village, Kebumen Regency. The research employs a qualitative-descriptive approach with data collection methods including observation, in-depth interviews, and documentation. Informants were selected purposively and consisted of BUMDes managers, village government officials, and community members directly involved in BUMDes activities. Data analysis was carried out through reduction, presentation, and conclusion drawing, validated through source and method triangulation. The findings reveal that the development of local wisdom through BUMDes involves five main stages: mapping of village potential, determining the community's collective vision, designing a development timeline, identifying stakeholders, and program implementation. Through the management of BUMDes, local potentials such as pandanus weaving crafts, traditional culinary tourism at Pasar Perengkali, organic rice cultivation, and various cultural activities have been successfully integrated in a synergistic manner. The positive impacts of BUMDes management are felt by the community in the form of increased economic income, the creation of new job opportunities, enhanced entrepreneurial independence both individually and collectively, and the more equitable distribution of income across the community. The study concludes by emphasizing the crucial role of BUMDes in developing local potential as a means of empowering the village economy. Participatory management based on local wisdom is identified as a key success factor in achieving independent and sustainable village development.